تجليات العنف السيبراني القائم على النوع الاجتماعي في الفضاءات الرقمية - مامة حمدي; صفاء فشكار; د/ شربالي حسين (جامعة عمار ثليجي بالاغواط, 2025)
ملخص الدراسة: تهدف هذه الدراسة إلى التعرف على طبيعة التفاعل الرقمي مع المنشورات النسوية في الفضاء الجزائري عبر موقع فيسبوك، من خلال دراسة تحليلية لتعليقات تم جمعها من صفحتين نسويتين نشيطتين. كما تهدف إلى الكشف عن تمثلات النوع الاجتماعي (الجندر) وتجليات العنف السيبراني ضد المرأة، من خلال تحليل فئوي دقيق يراعي الجانبين الشكلي والمضموني للتعليقات. تم الاعتماد على أداة تحليل المضمون من خلال استمارة أُعدت خصيصًا لهذه الدراسة، حيث شملت فئات تتعلق بالأسلوب، اللغة، نمط التفاعل، الطابع العام، بالإضافة إلى فئات مضمونية مثل الموضوع، العنف السيبراني، الصور النمطية، القيم السلبية وغاية التفاعل. وقد بلغ حجم العينة 60 تعليقًا (30 تعليقًا من كل صفحة)، تم اختيارها بطريقة عشوائية بسيطة. تندرج الدراسة ضمن الدراسات الوصفية التحليلية، حيث تم الجمع بين التحليل الكمي والكيفي، من أجل الوصول إلى فهم شامل لطبيعة الخطاب الرقمي الموجّه نحو المرأة. وقد توصّلنا من خلال التحليل إلى جملة من النتائج، من أبرزها: • غلبة الطابع السلبي على التفاعل الرقمي في كلا الصفحتين. • التركيز الكبير على سلوك المرأة أكثر من مظهرها أو ظروفها. • تكرار الصور النمطية التقليدية للمرأة كضحية أو متمردة. • بروز العنف السيبراني بمختلف أشكاله، خاصة السخرية والتهكم. • غياب التوازن في الخطاب بين النقد والدعم. • سيطرة اللغة الدارجة على أغلب التعليقات، مع حضور محدود للفصحى. الكلمات المفتاحية: النوع الاجتماعي، العنف السيبراني، الفضاء الرقمي، التفاعل، المرأة، الجندر. Abstract : This study aims to explore the nature of digital interaction with feminist posts within the Algerian online space, specifically on Facebook, through an analytical examination of comments collected from two active feminist pages. The objective is to uncover representations of gender and manifestations of cyber violence against women, using a detailed categorical analysis that considers both formal and content-related aspects of the comments. The study relied on content analysis as a methodological tool, using a form specifically designed for this purpose. The categories included aspects such as style, language, interaction type, and general tone, as well as thematic categories like subject matter, cyber violence, stereotypes, negative values, and the purpose of interaction. The sample consisted of 60 comments (30 from each page), selected using a simple random sampling method. This research falls under descriptive and analytical studies, combining both quantitative and qualitative approaches to provide a comprehensive understanding of the nature of digital discourse directed toward women. The analysis led to several key findings, including: • A predominantly negative tone in digital interactions across both pages. • A strong focus on women’s behavior rather than their appearance or circumstances. • Recurrent traditional stereotypes portraying women either as victims or rebels. • Various forms of cyber violence, particularly mockery and sarcasm. • A lack of balance between criticism and support in the discourse. • The dominance of colloquial language in most comments, with limited use of formal Arabic. Keywords: Gender, Cyber Violence, Digital Space, Interaction, Women, Gender Representations.
دراسة تحليلية لتعليقات الصفحات النسائية